2014
DOI: 10.5694/mja13.00104
|View full text |Cite
|
Sign up to set email alerts
|

The high burden of inpatient diabetes mellitus: the Melbourne Public Hospitals Diabetes Inpatient Audit

Abstract: Objective: To determine the prevalence of diabetes in inpatients in Melbourne hospitals. Design: Point prevalence survey of all inpatients in each hospital on a single day between 30 November 2010 and 22 November 2012. Setting: 11 hospitals in metropolitan Melbourne including community, secondary and tertiary hospitals and one aged care and rehabilitation centre. Participants: 2308 adult inpatients in all wards apart from intensive care, emergency, obstetrics and psychiatry. Main outcome measures: Point preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 11 publications
(6 reference statements)
8
75
1
1
Order By: Relevance
“…Our study highlights the high indirect attributable burden of DM on hospitalisation costs. Although limited to a subgroup of non‐surgical, non‐obstetric hospitalised adults, the 33% DM prevalence in GIM patients accorded well with previously documented DM prevalence throughout our entire Health Service . We found that, following adjustment for confounders, patients with comorbid DM had a 1.22‐fold higher ICC and 1.19‐fold increased odds of staying longer in hospital.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study highlights the high indirect attributable burden of DM on hospitalisation costs. Although limited to a subgroup of non‐surgical, non‐obstetric hospitalised adults, the 33% DM prevalence in GIM patients accorded well with previously documented DM prevalence throughout our entire Health Service . We found that, following adjustment for confounders, patients with comorbid DM had a 1.22‐fold higher ICC and 1.19‐fold increased odds of staying longer in hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed recent studies in our setting have shown that this approach may underestimate the real prevalence of diabetic complications (that approaches 80% when determined by a carefully structured interview). Therefore, our comparisons between these two groups should be interpreted cautiously …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that approximately one-third of general inpatients aged >54 years admitted to our hospital had type 2 diabetes (4). A recent Melbourne Public Hospitals Diabetes Inpatient Audit revealed the prevalence of diabetes ranged from 16 to 35% in different hospitals across the greater metropolitan region (5). …”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Melbourne hospitals found that the prevalence of diabetes in hospitalised patients ranged from 15.7 % to 35.1 %, and over 82 % of diabetes patients suffered from microvascular or macrovascular complications [67].…”
Section: Chapter 2 -Glycated Haemoglobin Literature Reviewmentioning
confidence: 99%